exoALMA. III. Line-intensity Modeling and System Property Extraction from Protoplanetary Disks - Andrés F. Izquierdo; Jochen Stadler; Maria Galloway-Sprietsma; Myriam Benisty; Christophe Pinte; Jaehan Bae; Richard Teague; Stefano Facchini; Lisa Wölfer; Cristiano Longarini; Pietro Curone; Sean M. Andrews; et al. (The Astrophysical Journal Letters)
The ALMA large program exoALMA offers a unique window into the three-dimensional physical and dynamical properties of 15 circumstellar disks where planets may be actively forming. Here, we present an analysis methodology to map the gas disk structure and substructure encoded in ^12 CO, ^13 CO, and CS line emission from our targets. To model and characterize the disk structure probed by optically thin species, such as CS and, in some cases, ^13 CO, we introduce a composite line profile kernel that accounts for increased intensities caused by the projected overlap between the disk’s front and back side emission. Our workflow, built on the discminer modeling framework, incorporates an improved iterative two-component fitting method for inclined sources ( i > 40 ^∘ ) to mitigate the impact of the disk back side on the extraction of velocity maps. Also, we report best-fit parameters for the Keplerian stellar masses, as well as inclinations, position angles, systemic velocities, rotation direction, and emission surfaces of the disks in our sample.